Genus-level revision of the family Phalacridae (Coleoptera: Cucujoidea) - Gimmel, Matthew L. (Zootaxa, 2013)
A pre-phylogenetic revision of the family Phalacridae at the genus level is presented. Twenty-eight new generic synonymies are established as follows: Acylomus Sharp 1888 (=Liophalacrus Sharp 1888, syn. nov.; Ganyrus Guillebeau 1894, syn. nov.; Podocesus Guillebeau 1894, syn. nov.; Tinodemus Guillebeau 1894, syn. nov.; Ledorus Guillebeau 1895, syn. nov.; Astenulus Guillebeau 1896, syn. nov.; Afronyrus Švec 2006, syn. nov.), Apallodes Reitter 1873 (=Litolibrus Sharp 1889, syn. nov.; Sphaeropsis Guillebeau 1893, syn. nov.; Gyromorphus Guillebeau 1894, syn. nov.), Augasmus Motschulsky 1858 (=Megischius Guillebeau 1896, syn. nov.; Nematolibrus Sahlberg 1913, syn. nov.), Entomocnemus Guillebeau 1894 (=Stilbomimus Champion 1924, syn. nov.), Grouvelleus Guillebeau 1892 (=Ochrolitoides Champion 1924, syn. nov.; Litotarsus Champion 1925, syn. nov.), Litochrus Erichson 1845 (=Merobrachys Guillebeau 1895, syn. nov.), Litostilbus Guillebeau 1894 (=Pseudolitochrus Liubarsky 1993, syn. nov.), Ochrolitus Sharp 1889 (=Gorginus Guillebeau 1894, syn. nov.), Olibroporus Casey 1890 (=Parasemus Guillebeau 1894, syn. nov.), Olibrosoma Tournier 1889 (=Lichrotus Lyubarsky 1993, syn. nov.), Phaenocephalus Wollaston 1873 (=Phalacratomus Scott 1922, syn. nov.; Heterostilbus Champion 1924, syn. nov.), Phalacrinus Blackburn 1891 (=Sphaerostilbus Champion 1924, syn. nov.), Pseudolibrus Flach 1889 (=Biophytus Guillebeau 1894, syn. nov.; Polyaloxus Guillebeau 1894, syn. nov.), Pycinus Guillebeau 1893 (=Ochrodemus Guillebeau 1893, syn. nov.; Radinus Guillebeau 1893, syn. nov.; Euphalacrus Champion 1925, syn. nov.). Ten new genera and seven new species are described: Antennogasmus, gen. nov. (type species: A. cordatus, sp. nov.), Austroporus, gen. nov. (type species: A. victoriensis (Blackburn)), Malagasmus Gimmel, gen. nov. (type species: M. thalesi, sp. nov.), Malagophytus, gen. nov. (type species: M. steineri, sp. nov.), Neolitochrus, gen. nov. (type species: N. pulchellus (LeConte)), Paracylomus, gen. nov. (type species: P. asiaticus (Champion)), Platyphalacrus, gen. nov. (type species: P. lawrencei, sp. nov.), Ranomafanacrinus, gen. nov. (type species: R. nigrinus, sp. nov.), Steinerlitrus, gen. nov. (type species: S. warreni, sp. nov.), Sveculus, gen. nov. (type species: S. lewisi, sp. nov.). Generic reassignments resulted in 194 new combinations. Nine new names have been established for junior primary and secondary homonyms: Acylomus bicoloratus nom. nov. for Tinodemus bicolor Švec 2002; Acylomus lyubarskyi nom. nov. for Olibrus capriviensis Lyubarsky 1998; Acylomus sveci nom. nov. for Tinodemus reticulatus Švec 2002; Acylomus orientalis nom. nov. for Stilbus similis Švec 1992; Acylomus zdeneki nom. nov. for Afronyrus snizeki Švec 2006; Apallodes championi nom. nov. for Litolibrus ocellatus Champion 1925; Olibrus peringueyi nom. nov. for Olibrus consanguineus Péringuey 1892; Augasmus exquisitus nom. nov. for Litochrus pulchellus Blackburn 1895; Litochrus pronotalis nom. nov. for Augasmus bimaculatus Lyubarsky 1996. A type species is designated for Phalacrinus Blackburn 1891 (P. australis Blackburn 1891). Six new species-group synonymies are established: Acylomus ergoti Casey 1890 (=Tinodemus grouvellei Guillebeau 1894, syn. nov.), Acylomus curvolineatus (Champion 1924) (=Tinodemus meridianus (Švec 1992), syn. nov.; Olibrus stuporatus Lyubarsky 1994, syn. nov.), Xanthocomus attenuatus (Casey, 1890) (=Xanthocomus concinnus (Casey, 1916), syn. nov.; Stilbus thoracicus Casey, 1916, syn. nov.; Stilbus quadrisetosus Casey, 1916, syn. nov.). One name, Olibrus sternalis Casey 1916, is resurrected from synonymy. Lectotypes are designated for 23 nominal species. One genus and two species are excluded from Phalacridae: Sternosternus Guillebeau 1894 (with its type and only species, S. grouvelleiGuillebeau 1894) and Parasemus parvopallidus Lea 1932, both of which belong in Hydrophilidae. All 34 resulting genera in the family Phalacridae are keyed, described, and illustrated. A phylogenetic hypothesis based on analysis of a matrix of 98 morphological characters was created using parsimony. Results of these analyses were not robust enough at deep levels to create a new subfamilial or tribal classification, but nine genus-groups have been hypothesized.